Learning styles and learning strategies in university students - Aguilar Rivera, María del Carmen (2010)
The relationship between learning (styles and learning strategies) by sex is studied, in a sample of students admitted to university aged 17-21. The theories and concepts related to measurements are explained. Results have educational implications, and reveal differences by sex in relation to how the processes and transformation of the information. Keywords: Learning styles, learning strategies, college students.